Design and Implementation of Bitrate Adaptation Schemes for Power Capping in Wi-Fi Video Streaming - Gyuwhan Kim; Dayoung Lee; Minseok Song (IEEE Access, 2020)
In dynamically adaptive streaming over HTTP (DASH), which is the de facto standard for streaming, each video is divided into segments, and each segment is further transcoded into multiple bitrate versions. This allows a client device to select the most appropriate bitrate version that matches the network bandwidth to avoid jitters or stalls. However, Wi-Fi download of a high-bitrate version may consume significant energy, especially when network conditions are good. To address this, we propose a new streaming method that limits the energy consumed by mobile devices but maintains an acceptable video quality. First, we derive a power model to analyze how bitrate selection affects power consumption in smartphones. Based on this, we propose two algorithms that determine the bitrate of each segment with the aim of maximizing overall video quality while limiting energy consumption. We use dynamic programming and heuristics to address the tradeoff between algorithm complexity and video quality. The proposed scheme was implemented on an Android-based DASH streaming platform, and various issues were resolved to cope with varying network conditions. Experimental results demonstrated that our scheme effectively optimized the video quality while limiting the energy consumption. For example: 1) our scheme uses 4% and 10% less power than DASH while maintaining an excellent video quality, and 2) the average difference between estimated and actual power consumption is 0.8%, thus keeping a precise energy bound.